2019
DOI: 10.1042/bsr20181215
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of gut barrier dysfunction in a trauma-hemorrhagic shock rat model

Abstract: Intestinal barrier dysfunction has been implicated in the development of multiorgan dysfunction syndrome caused by the trauma-hemorrhagic shock (THS). However, the mechanisms underlying THS-induced gut barrier injury are still poorly understood. In the present study, we used the metabolomics analysis to test the hypothesis that altered metabolites might be related to the development of THS-induced barrier dysfunction in the large intestine. Under the induction of THS, gut barrier failure was characterized by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Gut metabolites are closely related to some intestinal and extraintestinal diseases, such as inflammatory bowel disease, irritable bowel syndrome, depression, and autism (Duboc et al, 2012;Bjerrum et al, 2015;Sharon et al, 2019;Keshteli et al, 2019). Moreover, some gut metabolites could protect or destroy the gut barrier (Li et al, 2019;Parada Venegas et al, 2019). In this study, the intestinal metabolite profiles were significantly different between the CA + DSS and CA + DSS + DADS groups.…”
Section: Discussionmentioning
confidence: 53%
“…Gut metabolites are closely related to some intestinal and extraintestinal diseases, such as inflammatory bowel disease, irritable bowel syndrome, depression, and autism (Duboc et al, 2012;Bjerrum et al, 2015;Sharon et al, 2019;Keshteli et al, 2019). Moreover, some gut metabolites could protect or destroy the gut barrier (Li et al, 2019;Parada Venegas et al, 2019). In this study, the intestinal metabolite profiles were significantly different between the CA + DSS and CA + DSS + DADS groups.…”
Section: Discussionmentioning
confidence: 53%
“…Glyceric acid is a product of the pentose phosphate pathway, and its abnormally high levels in tissues can cause metabolic acidosis. And the pentose phosphate pathway can promote the production of reducing equivalents, such as NADPH, which will be used for reducing biosynthesis reactions in cells ( Sun et al, 2017 ; Li Z. et al, 2019 ). Based on the previous results, our current results suggests that mice from the abdominal irradiation group may have a certain degree of hyperoxidation, which is consistent with the previously reported bystander effect of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Succinic acid, citrate and malic acid are three important metabolic intermediates in the TCA. Succinic acid is involved in various biological processes such as ATP biosynthesis and signal transduction (Li et al, 2019). These three TCA intermediates increased during HS and recovery to different degrees after blood transfusion, which is consistent with previous reports in the literature, suggesting that they can be used as biomarkers for reperfusion injury (D'Alessandro, Slaughter, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…If the treatment is not rapid enough, it will result in death owing to multiple organ function injury. It is reported that it is one of the main causes of death among trauma victims, accounting for about 40% of deaths (Li et al, 2019). Plasma contains a large number of proteins and can compensate for the fluid loss caused by HS and increase the supply of oxygen and nutrients in tissues; therefore, timely blood transfusion is one of the common methods to treat hemorrhagic shock (Traverso, Medina, & Bolin, 1985).…”
Section: Introductionmentioning
confidence: 99%